inovasi aplikasi pembelajaran pendidikan agama islam di sekolah menegah atas (SMA) - Farah Hanifah diah; Hana Khofifah; Henti Fauziah; Muhamad Wisnu; Fiqra Nazib (Yayasan Al-Afif, 2024)
This research aims to investigate innovations in Islamic Religious Education (PAI) learning applications at the Senior High School level. This study employs a literature review system, wherein the researcher examines several existing research findings. The research process involves several steps, including determining the title, searching, and selecting literature. In this research, 53 articles were selected from a total of 70 obtained from various sources, published between 2019 and 2024. The focus of this study is on three aspects: implementation, innovation, and implications of using applications in PAI learning at the Senior High School level. The results show that: 1) the implementation process of PAI learning applications in senior high schools involves the use of various applications to enhance the effectiveness of learning activities; 2) there are innovations in PAI learning applications; and 3) the use of applications in PAI learning has its own impacts, both positive and negative.